2014
DOI: 10.1097/prs.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mouse Mast Cell Proteases in the Proliferative Phase of Wound Healing in Microdeformational Wound Therapy

Abstract: Results suggest that mouse mast cell proteases 4, 5, and 6 are mediators of the critical role mast cells play in microdeformational wound therapy in the proliferative phase of healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Their dorsum was disinfected with 70% alcohol and marked with standard square template (1.0 cm 2 ). Skin plus panniculus carnosus was excised to create a full-thickness dorsal excisional wound, which was covered with transparent, semiocclusive adhesive polyurethane dressings (Tegaderm; 3M, St. Paul, MN) and changed two times per week (3032). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their dorsum was disinfected with 70% alcohol and marked with standard square template (1.0 cm 2 ). Skin plus panniculus carnosus was excised to create a full-thickness dorsal excisional wound, which was covered with transparent, semiocclusive adhesive polyurethane dressings (Tegaderm; 3M, St. Paul, MN) and changed two times per week (3032). …”
Section: Methodsmentioning
confidence: 99%
“…Standardized photographs were taken on the day of surgery and on the 3rd, 7th, 10th, and 14th days for 14 days from a standard height. Re-epithelialization and open wound surface were measured as a percentage of the initial wound area as published (3032). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On days 0, 3, 6, 9, 12, and 15 after surgery, reepithelialization of the wound was monitored macroscopically (assessed on the basis of the absence of redness and fluid exudate), and the wound's open area was digitally photographed. On days 9 and 15 after surgery, wounds from 6 animals in each group were harvested as previously described (58). In another series of experiments, fibroblasts from controls were infected with either adenoviral vectors containing GFP (Ad-GFP) or with WT PKCδ isoforms (Ad-wtPKCδ).…”
Section: Histological and Immunohistochemical Analysesmentioning
confidence: 99%
“…By contrast, the role of MCs in skin wound healing is controversial. Whereas some studies indicate that MCs are essential in certain models of wound healing (9)(10)(11)(12), others found that skin wound closure may not be affected by the absence of MCs (13)(14)(15).…”
mentioning
confidence: 99%